Lithological Classification and Environment of Deposition of the Khussak Formation, Khewra Gorge, Salt Range; Khewra - Khan, Muhammad Attaullah (Journal of Himalayan Earth Sciences, 1971)
The Khussak Formation (Early Cambrian), exposed in the Khewra gorge, shows rapid variations in lithology from its base towards top. Lithologically, the Khussak Formation can be conveniently divided into three members, (I) Lower Mudstone-Siltstone-Sandstone Member, (2) Middle Shale Member, and (3) Upper Mudstone-siltstone-sandstone Member. Interbeddings of dark gray micaceous shale occur at various stratigraphic levels within the Lower and Upper members. Layers with glauconite concentrations, which are traceable over fairly long distances, are fairly persistent in both the Lower and Upper members. The glauconite is conspicuously lacking in the Middle Shale Member. The Khussak Formation indicates deposition in a restricted marine basin, which became shallow from time to the and recorded low sedimentation. The overwhelmingly dark pray and grayish-green colours of the formation, layers with glauconite concentrations, crawling marks; and rare sun cracks on the surfaces of the interbedded siltstone and sandstone support the above statement. Occurrence of only phosphatic shells of brachiopods, characterized by their dwarfed nature, is an undeniable evidence for the existence of a restricted marine basin in which the Khussak Formation was deposited during the Early Cambrian Period.